ISLAMIC EPISTEMOLOGY IN THE THOUGHT OF ḤASAN ḤANAFĪ AND FAZLUR RAHMAN ON THE GENEALOGY OF ḤADĪTH - Daffa, Muhammad; Utomo, Agus Himmawan (Sekolah Tinggi Agama Islam Sadra, 2025)
This article examines the genealogical dimensions of ḥadīth within Islamic epistemology, with a focus on the comparative perspectives of Ḥasan Ḥanafī and Fazlur Rahman. The study recognizes that ḥadīth functions as a textual corpus and a dynamic epistemic source shaped by historical, ideological, and sociocultural forces. The primary objective is to explore how both thinkers conceptualize the genealogy and interpretation of ḥadīth as integral to the development of Islamic epistemology. Employing a qualitative library research method, this study applies genealogical analysis and comparative hermeneutics, grounded in the sociology of knowledge and testimonial epistemology theoretical frameworks. The findings reveal that Ḥanafī frames ḥadīth as a socio-political construct embedded within power relations and ideological structures, requiring critical deconstruction for emancipatory purposes. Conversely, Rahman situates ḥadīth within a moral-historical paradigm, emphasizing the role of ijtihād and the living Sunnah in extracting ethical values applicable to contemporary contexts. Both scholars reject the notion of a static, dogmatic ḥadīth tradition and instead propose interpretative methodologies that are historically conscious and socially responsive. The study concludes that integrating genealogical critique and epistemological reconstruction opens new avenues for revitalizing Islamic thought. It expands the discourse on ḥadīth beyond traditional jurisprudential confines, offering a dynamic framework for engaging with prophetic traditions in modern intellectual contexts.